A methodology for assessing and managing university awareness in the digital environment: A case of Russia’s federal districts - Aliya A. Gataullina; Alina F. Garyaeva; Alina A. Zyabbarova (Управленец)
In the context of digitalization, a strong image of a university based on values, mission and unique features is a key factor influencing popularity in cyberspace. The article develops a methodology for assessing university awareness in the digital environment and determining its reputation through analysing the frequency of web queries in the Yandex search engine. The entrepreneurial university concept constitutes the theoretical framework of the study. The research method is a quantitative approach to statistical analysis of a continuous array of text data. Empirical data include official regulations on educational insti tutions, data from the Ministry of Education and Science of the Russian Federation and the Federal State Statistics Service (Ross tat), and Yandex digital analytics. Our methodology involves assessing university names popular in cyberspace and comparing quantitative indicators of universities’ digital reputation. The paper presents Russia’s top-20 universities with highest awareness levels based on search queries, and the top-10 universities for all Russia’s federal districts (FDs). Six out of eight districts (exclud ing the Southern and North Caucasus FDs) are represented in the top-20 universities ranking. The Central FD, especially Moscow, generate the largest number of queries, which may indicate a high interest in the capital’s universities. The study specifies reputa tional risks associated with universities’ names in the charters, namely ambiguous abbreviations and a limited number of options. To avoid confusion, it is necessary to single out unique names and abbreviations and formalize the most common of them. One particular name should be used to enhance university awareness and attractiveness, which reduces reputational risks and, thus, creates a strong university image.